2021
DOI: 10.14421/biomedich.2021.102.73-79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus and Hypertension on Osmotic Fragility and Hemorheological Factors in Male Wistar Rats

Abstract: Diabetes mellitus is a common risk factor for erythrocyte osmotic stress. This study was aimed at exploring the effect of streptozotocin (STZ)-induced diabetes mellitus and salt-induced hypertension on osmotic fragility and hemorheological variables in male Wistar rats. Thirty male rats were grouped into five groups of six animals each as follows: negative control (zero salt in diet); positive control (normal salt diet - 0.3% salt); high salt diet (8% salt) (HSD only); STZ induced diabetes and normal salt diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Normoglycemia is a major aim in diabetes that must be met in order to avoid organ damage and inflammation caused by persistently high blood sugar levels [36,15,25,37] Streptozotocin is an antibiotic that inhibits the production of insulin, a peptide hormone responsible for the conversion of glucose to glycogen in the liver, by targeting the beta cells of the pancreas. Reduced insulin production or insulin receptor insensitivity has been linked to impaired glucose utilization [25,37,22]. In line with prior research, our investigation found a drop in serum insulin in the diabetes control group, resulting in the diabetes phenotype seen in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Normoglycemia is a major aim in diabetes that must be met in order to avoid organ damage and inflammation caused by persistently high blood sugar levels [36,15,25,37] Streptozotocin is an antibiotic that inhibits the production of insulin, a peptide hormone responsible for the conversion of glucose to glycogen in the liver, by targeting the beta cells of the pancreas. Reduced insulin production or insulin receptor insensitivity has been linked to impaired glucose utilization [25,37,22]. In line with prior research, our investigation found a drop in serum insulin in the diabetes control group, resulting in the diabetes phenotype seen in this study.…”
Section: Discussionsupporting
confidence: 90%
“…"Phytochemicals found in various plantbased components, such as vitamins, polyphenols, tannins, flavonoids, saponins, terpenes, and sterols, can boost the body's antioxidant defence mechanism" [21,18]. "However, a large number of studies have suggested that phyto-bioactive compounds with high antioxidant activity may have a variety of biological effects, including influencing glucose absorption and uptake, modulating insulin secretion, and managing or reducing the risk of developing DM complications" [4,14,22]. "Dryopteris dilatata is one of the plants used to treat health problems and the Dryopteris dilatata, popularly known as the 'Broad buckler fern,' is a member of the Dryopteridaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Deteriorating kidney functions are most frequently caused by diabetes in Nigeria (Okaka et al, 2020;Ibitoba et al, 2022). Diabetic and hypertensive patients also have increased prevalence of cardiovascular (CV) risk factors, such as dyslipidemia, microalbuminuria, hyperuricemia, a propensity to clot, and left ventricular hypertrophy (Mantovani et al, 2020;Sanusi et al, 2020;Okonofua et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is paramount to induce type 2 diabetes mellitus as the mechanisms of hypoglycaemic action of metformin and glibenclamide involves available beta cells [54]. Diabetic state of the rats was checked after 72 h by means of a glucometer (ACCU-CHEK ® Active) and compatible blood glucose test strips, and animals with hyperglycaemia of fasting blood glucose level of ≥ 200 mg/dl were selected for the study [55,56].…”
Section: Induction Of Diabetes and Hypertensionmentioning
confidence: 99%